Finance and Development, March 2019. (Finance and Development; Finance and Development, 2019)
This issue of Finance and Development discusses need of empowering women, which is critical for the world's economy and people. Unequal or unfair treatment can marginalize women and hinder their participation as productive individuals contributing to society and the economy in invaluable ways. The rich tapestry of organizations and individuals who can make a difference to ensure women have equal opportunities; there is a crucial role for policymakers. They can use their positions to design policies that help women and girls' access what they need for a fulfilling life-including education, health services, safe transportation, legal protection against harassment, finance, and flexible working arrangements. The IMF recommends these kinds of policy measures to its member countries-and works with many governments to examine how policies affect women. The IMF's 189 member countries face many different challenges, but empowering women remains a common denominator and a global imperative for all those who care about fairness and diversity, but also productivity and growth of societies and economies that are more inclusive.